Karakteristik Pendonor Yang Mengalami Penundaan Donor Darah Karena Faktor Hemoglobin Di UDD PMI Kabupaten Bojonegoro Tahun 2019-2022 - Sudiwati, Ni Luh Putu Eka; Tarwiyanida, Annisa; Panggayuh, Ardi; Ariani, Nia Lukita; Saefudin, Asep; Sutrisno, Imam (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
The availability of blood with unbalanced blood needs causes blood service facilities to lack blood stock. The deferral in donating blood is one of the reasons for the shortage of blood stock. The purpose of this study was to determine the characteristics of donors who experienced deferral in donating blood due to haemoglobin levels at UDD PMI Bojonegoro Regency in 2019–2022. The research design used is descriptive-quantitative through a secondary data survey. Data was obtained from the SIMDONDAR application regarding the number and characteristics of donors who experienced deferral in donor selection due to haemoglobin levels at UDD PMI Bojonegoro Regency during the 2019–2022 period. The data were analysed descriptively and presented in the form of tables and graphs. The results showed that the delay in donor selection was due to haemoglobin levels at UDD PMI Bojonegoro Regency for the 2019–2022 period, with as many as 3,385 donors with low haemoglobin levels totaling 2,492 people and 893 people with high haemoglobin levels. Characteristics of donors who experience delays in donating blood due to haemoglobin levels at UDD PMI Bojonegoro Regency in 2019–2022, based on age: most occur at the age of 25–44 years with a total of 198 people (51%); the most gender is female with a total of 208 people (54%); blood type occurs in O (+) in 148 people (38%); and type of work occurs in private employees in 138 people (36%).